Etiologic Framework for the Study of Neurodegenerative Disorders as Well as Vascular and Metabolic Comorbidities on the Grounds of Shared Epidemiologic and Biologic Features - de Pedro-Cuesta, Jesús; Martínez-Martín, Pablo; Rábano, Alberto; Ruiz-Tovar, María; Alcalde-Cabero, Enrique; Calero, Miguel (Frontiers in Aging Neuroscience, 2016)
Background: During the last two decades, protein aggregation at all organismal levels, from viruses to humans, has emerged from a neglected area of protein science to become a central issue in biology and biomedicine. This article constitutes a risk-based review aimed at supporting an etiologic scenario of selected, sporadic, protein-associated, i.e., conformational, neurodegenerative disorders (NDDs), and their vascular- and metabolic-associated ailments. Methods: A rationale is adopted, to incorporate selected clinical data and results from animal-model research, complementing epidemiologic evidences reported in two prior articles. Findings: Theory is formulated assuming an underlying conformational transmission mechanism, mediated either by horizontal transfer of mammalian genes coding for specific aggregation-prone proteins, or by xeno-templating between bacterial and host proteins. We build a few population-based and experimentally-testable hypotheses focusing on: (1) non-disposable surgical instruments for sporadic Creutzfeldt-Jakob disease (sCJD) and other rapid progressive neurodegenerative dementia (sRPNDd), multiple system atrophy (MSA), and motor neuron disease (MND); and (2) specific bacterial infections such as B. pertussis and E. coli for all forms, but particularly for late-life sporadic conformational, NDDs, type 2 diabetes mellitus (T2DM), and atherosclerosis where natural protein fibrils present in such organisms as a result of adaptation to the human host induce prion-like mechanisms. Conclusion: Implications for cohort alignment and experimental animal research are discussed and research lines proposed.